Emotions Attributions of ELT Pre-service Teachers and Their Effects on Teaching Practice - Mariza G. Méndez López (Universidad Nacional de Colombia, 2020)
This article presents the results of a qualitative study which aimed to develop an understanding of the emotions experienced by pre-service English language teachers during their teaching practicum and the emotions' effects on instructional teaching. Attribution theory was used as a framework for analysing the results, while the data were gathered through classroom observation, reflection journals, and semi-structured interviews. Results revealed a need for language teaching programmes to include classroom management strategies; however, there is also evidence of the urgent need for socio-emotional support to be provided to pre-service teachers to help them shape their teaching practice through reflection. Providing a space for pre-service teachers to reflect on their beliefs and discuss the emotions experienced during practicum may help to instil commitment and responsibility in future teachers.